6 Comparison ctca dose audit between initial service development and subsequent service establishment phase for a dgh ctca service. (15th May 2019) - Kalamar, Vilim; Chapman, Peter; Elford, Julian; Fleet, Jade; Wright, Alison; Crawley, Zoe
Abstract : Introduction: The delivery of computed tomography coronary angiography (CTCA) services is variable but underprovided across the UK. Hampshire hospitals foundation trust (HHFT) is trying to contribute to this necessary national increase in CTCA provision. The aim of this poster presentation is presentation of our initial ionizing radiation dose audits for governance and to share issues we faced locally which might be relevant to other sites starting similar services. Methods: Retrospective analysis of all patients attending HHFT for CTCA at HHFT was obtained by interrogation of the Computerized Radiology Information System (CRIS) database between 2013 and April 2018, then re-audited between May 2018 and February 2019.The total Dose-Length Product (DLP) units (mGycm) and heart rate at time of acquisition were identified allowing comparison between the initial service development & second service establishment phase. Results: The median total DLP was 113.11 during initial service development (January 2013 – April 2018 phase). The median total DLP was 192.91 during service establishment phase (May 2018 – February 2019) Median DLP became higher in establishment phase. Conclusion: Initial success of the service along with initial tight patient selection led to a lower first round DLP. Subsequent appointment of an Electrophysiology Cardiology Consultant and increasing awareness of service led to evolving referral patterns with more atrial fibrillation (AF) ablation scans requested. Identifying this in the second round of audit has led to discussions with referrers & establishment of routine DLP recording onto CRIS